RANCANG BANGUN SISTEM MONITORING SUHU DAN KELEMBABAN PADA PERKEBUNAN KOPI DENGAN METODE WIRELESS SENSOR NETWORK (WSN) - Mohammad, Akmal Rozan; Maulana, Eka; Nusantoro, Goegoes Dwi (Jurnal Mahasiswa TEUB, 2024)
As a developing country, Indonesia strives to become a developed nation through economic transformation, including increasedproductivity in the plantation sector, particularly coffee. Coffee plays a crucial role in Indonesia's economy, significantlycontributing to non-oil exports. In 2022, Indonesia became the third-largest coffee producer in the world. However, domestic coffee production still falls short of meeting the growing demands for consumption and export. Coffee plant growth is influenced by factors such as water availability and tree shade. Adequate rainfall is essential for optimal growth, affecting the temperature and humidity, which in turn impacts coffee production. High temperatures can cause flower drop and reducing yield. This study addresses these conditions by designing a monitoring system capable of detecting temperature and humidity in coffee plantations. Utilizing wireless sensor network (WSN) technology, this system is developed to monitor large areas and display the results in spreadsheets. The system comprises a DHT22 sensor for measuring air temperature and humidity, a YL69 sensor for soil moisture, and a LoRa SX1278 for long-range communication. The results indicate that the designed system operates effectively, providing accurate data with an error rate of 4.81% for the YL69 sensor, 0.87% for the DHT22 temperature measurements, and 1.04% for humidity measurements. The LoRa communication system has a maximum range of 360 meters. Keywords: Coffee, Temperature and Humidity, LoRa, WSN